Answer:Given below
Step-by-step explanation:
Using mathematical induction
For n=1
[tex]2!=2^1[/tex]
True for n=1
Assume it is true for n=k
[tex]2!\cdot 4!\cdot 6!\cdot 8!.......2k!\geq \left ( k+1\right )^{k}[/tex]
For n=k+1
[tex]2!\cdot 4!\cdot 6!\cdot 8!.......2k!2\left ( k+1\right )!\geq \left ( k+1\right )^{k}\dot \left ( 2k+2\right )![/tex]
because value of [tex]2!\cdot 4!\cdot 6!\cdot 8!.......2k!=\left ( k+1\right )^{k}[/tex]
[tex]\geq \left ( k+1\right )^{k}\dot \left ( 2k+2\right )![/tex]
[tex]\geq \left ( k+1\right )^{k}\left [ 2\left ( k+1\right )\right ]![/tex]
[tex]\geq \left ( k+1\right )^{k}\left ( 2k+\right )!\left ( 2k+2\right )[/tex]
[tex]\geq \left ( k+1\right )^{k+1}\left ( 2k+\right )![/tex]
Therefore [tex]2!\cdot 4!\cdot 6!\cdot 8!.......2k!2\left ( k+1\right )! must be greater than \left ( k+1\right )^{k+1}[/tex]
Hence it is true for n=k+1
[tex]2!\cdot 4!\cdot 6!\cdot 8!.......2k!2\left ( k+1\right )!\geq \left ( k+1\right )^{k+1}[/tex]
Hence it is true for n=k